An Integrated Survey of the Geochemical Study at the Blawan-Ijen Area, East Java - Riska Laksmita Sari; Firman Sabila; Haeruddin Haeruddin; Eriska Saputri; Welayaturromadhona Welayaturromadhona; Hadziqul Abror; Sartika Purwandari; Agus Triono (Universitas Islam Riau (UIR) Press, 2021)
Geothermal energy is a renewable alternative energy source. One of the analyses used to determine the characteristics of a geothermal field is water geochemical analysis. The target of this research is the Blawan-Ijen geothermal prospect area, Bondowoso. The geochemical analysis was carried out using AAS, Spectrophotometer and acid-base titration. This survey shows the characteristics of the geothermal system and geothermal fluid in the Blawan area, Ijen. From the chemical analysis of hot water, we found that the types of geothermal water fluids in the Blawan Ijen area vary. In samples BL1, BL2 and BL5 included in the type of Sulphate Water with the dominant elemental Sulphate (SO4) content is also known as Sulfuric Acid Water (Acid-Sulphate Water). Then for the BL4 sample included in the type of chloride water. This type of water is a type of geothermal fluid found in most areas with high-temperature systems. Areas with large-scale hot springs flowing with high Cl concentrations originate from deep reservoirs and indicate permeable zones in those areas. However, this area may not be located above the main upflow zone. There are several other possibilities, such as topographic influences, which can significantly impact hydrological control. The presence of chlorine gas can also identify high zones' permeable areas (e.g., faults, breccia eruptions or conduit). In contrast, BL3 samples are included in the Bicarbonate Water-type. The element HCO3 (bicarbonate) is the most dominant element (main anion) and contains CO2 gas from the chemical analysis results. HCO3 water is generally formed in marginal and near-surface areas in systems dominated by volcanic rocks, where CO2 gas and condensed water vapour into groundwater. The vapour condensation can either heat the groundwater or be heated by steam (steam heated) to form an HCO3 solution